Infrared Absorption Cross Sections of ClOOCl - Laboratory Work and Application in MIPAS-B Measurements - Birk, M.; Wagner, G.; Oelhaf, H.; Wetzel, G. (2010)
Chlorine peroxide, ClOOCl, is involved in the ozone depletion cycle in polar perturbed chemistry (e.g. antarctic ozone hole). Despite the importance there has been no direct detection of this molecule in the atmosphere due to the missing spectroscopic database and rather weak atmospheric infrared spectra. The first part of the present paper will report on work on mid infrared absorption cross sections of ClOOCl already done in 2000. ClOOCl was produced in a flow reaction of Cl and Cl2O via ClO self reaction below 260 K. Number densities were derived from far infrared measurements utilizing intensities of pure rotational transitions. Measurements were carried out with a high resolution Bruker IFS120HR Fourier-transform spectrometer. A coolable 80 m absorption path multireflexion cell was applied for the subsequent FIR/MIR measurements. Although high resolution structure was partly resolved due to the high complexity (heavy molecule, four isotopologues, internal rotation) absorption cross sections at two different temperatures and total pressures were measured and supplied as spectroscopic database. The second part will show the first direct atmospheric observations of ClOOCl from MIPAS-B (Michelson Interferometer for Passive Atmospheric Sounding) balloon-based measurements from Kiruna (Sweden) on 11 January 2001 and 20/21 March 2003 with nighttime values of nearly 1.1 ppbv at 20 km.